Genome-wide identification of novel ovarian-predominant miRNAs: new insights from the medaka (Oryzias latipes) - Bouchareb, A; Le Cam, A; Montfort, J; Gay, S; Nguyen, T; Bobe, J; Thermes, V (Nature Publishing Group, 2017)
MicroRNAs (miRNAs) are small, highly conserved non-coding RNAs that play important roles in the regulation of many physiological processes. However, the role of miRNAs in vertebrate oocyte formation (i.e., oogenesis) remains poorly investigated. To gain new insights into the roles of miRNAs in oogenesis, we searched for ovarian-predominant miRNAs. Using a microarray displaying 3,800 distinct miRNAs originating from different vertebrate species, we identified 66 miRNAs that are expressed predominantly in the ovary. Of the miRNAs exhibiting the highest overabundance in the ovary, 20 were selected for further analysis. Using a combination of QPCR and in silico analyses, we identified 8 novel miRNAs that are predominantly expressed in the ovary, including 2 miRNAs (miR-4785 and miR-6352) that exhibit strict ovarian expression. Of these 8 miRNAs, 7 were previously uncharacterized in fish. The strict ovarian expression of miR-4785 and miR-6352 suggests an important role in oogenesis and/or early development, possibly involving a maternal effect. Together, these results indicate that, similar to protein-coding genes, a significant number of ovarian-predominant miRNA genes are found in fish.